Ginger And Citrus Aromatherapy For Servical Cancer Patients Post Chemotherapy - Adhisty, Karolin; Rizona, Firnaliza; Hudiyati, Maya (Universitas Aisyah Pringsewu, 2021)
Nausea and vomiting after chemotherapy is one of the effects that can reduce the patient'sspiritual biopsychosocial factor. The first purpose of this study was to determine the effect of aromatherapy inhalation in ginger and citrus. The second one to compare the value of both citrus and ginger aromatherapy to reduce effect of nausea and vomiting. This research was an experimental study with four solomon group designs. A sample of 68 respondents were divided into four groups by purposive sampling. Ginger aromatherapy showed p 0.002 less than alpha 0.05 and citrus aromatherapy showed p 0.009 less than alpha 0.05. These results indicate that both aromatherapy can reduce nausea and vomiting.The second analysis used the Mann-Whitney statistical test to compare the effect on the intervention group of each inhalation aromatherapy. The results showed that the p-value (0.192) more than alpha (0.05), which means that statistically there is no difference in the average score of nausea and vomiting between the intervention groups of ginger aromatherapy and citrus aromatherapy, but ginger aromatherapy can reduce nausea and vomiting by a difference mean 3.18 greater than citrus aromatherapy. Nurses can use ginger and citrus aromatherapy as an alternative solution to reduce nausea and vomiting in improving the patient's physical condition.